The symbolic construction of sports betting products. Issue 3 (2nd September 2021) - Lopez-Gonzalez, Hibai; Griffiths, Mark D.; Jimenez-Murcia, Susana
ABSTRACT: Numerous studies have explored the specific risk factors of sports betting attending to the singularities of sports bettors. However, many of these are also present in other gambling profiles (e.g. younger age, males, higher education, skill-based gambling) and fail to tackle the essentially distinguishing trait of sports betting, namely, its symbolic association with sport. This conceptual paper argues that sports betting draws from a rich pool of meanings from professional sport that influences how sports betting products are understood. It argues that, unlike other gambling products whose symbolic covering has to be built after, sports betting relies on a preexisting symbolic pool that structures its social significance. Sport confers to sports betting attributes of agency, control, and skill that make betting products more skill-oriented and less chance-based, but also other attributes of health, game, fun, and nature that decrease the perceived risks associated with sports betting. The paper contends that the symbolic association of sport and sports betting poses particular barriers for treatment of gambling disorder in the form of resistant cognitions about winning because professional sport embodies narratives of success deeply engraved in modern society, to an extent other gambling forms cannot compete in creating via their marketing strategies.